Frontiers in Geotechnical Engineering - Latha G., Madhavi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains contributions by eminent researchers in the field of geotechnical engineering. The chapters of this book are based on the keynote and theme lectures delivered at the Indian Geotechnical Conference 2018, and discuss the recent issues and challenges, while providing perspective on the possible solutions and future directions. A strong emphasis is placed on proving connections between academic research and field practice, with many examples and case studies. Topics covered in this volume include contemporary infrastructural challenges, underground space utilization, sustainable construction, dealing with problematic soils and situations and geo-environmental issues including landfills. This book will be of interest to researchers, practitioners and students alike.
Soft Ground Improvement- Experimental, Numerical and Field Studies -- Recommended practice for soft clays characterization with a focus on settlement and stability calculations -- Estimation of Dredged Fill Volume Based on Self-Weight Consolidation Characteristics of Dredged Soil -- A New Geomechanical Classification System for Weathered Volcanic Rocks -- Innovative geotechnical solutions worldwide -- Centrifuge model studies on the performance of geosynthetic reinforced soil structures -- Testing mode and soil behavior -- Seismic behaviour of tunnel and foundation systems in soft soils -- Foundations for Tall Buildings - Geotechnical Aspects -- Issues of Site Characterization in Seismic Analysis of Ground -- A Holistic Approach for the Stabilisation of Large Steep Slopes in a Jointed Rock Mass - A Case Study of Chenab Bridge -- Sustainable geotechnics- A biogeotechnological perspective -- Geotechnical Education from Field -- Liquefaction and Dynamic Properties of Scrap-Tyre Soil Mixtures -- Dynamiccharacterization of soils using various methods for seismic site response studies -- Reflection Crack Assessment using Digital Image Analysis' -- Recent Developments in Earth Pressure Reduction Techniques -- Dynamic Characterization of Rock and Its Application in Blast Analysis of Tunnels -- Insights into Contaminant Transport Modeling through Compacted Bentonites -- Probabilistic Study on the Geotechnical Behavior of Fiber reinforced Soil -- How vigilant professionals should be during investigation, design & construction? - a case study with respect to solar projects.
Keywords: Engineering geology; Geotechnical engineering; Buildings -- Design and construction; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Building Construction and Design